Potent antihypertensive activity of Thai-Lanna medicinal plants and recipes from "MANOSROI III" database - Manosroi A. (2014)
Context: Traditional medicines have long been used by Thai practitioners for the treatment of many diseases including hypertension. The antihypertensive recipes and plants were searched and selected by a computer program from Thai/Lanna medicinal plant recipe database "MANOSROI III" using hypertensive symptoms as keywords. Objectives: To evaluate the antihypertensive potential of 30 recipes and 10 Thai-Lanna medicinal plants selected from "MANOSROI III" database using l-NAME induced hypertensive rat model. Materials and methods: Extracts from the selected recipes and plants were prepared according to the traditional indications. Antihypertensive activities including the decrease of the mean arterial blood pressure (MABP) and heart rate (HR) of the extracts as well as duration of action were investigated by intra-arterial assessment technique. All extracts were screened for phytochemicals including anthraquinone, glycoside, xanthone, tannin, carotenoid, flavones and alkaloids using standard methods. Results and conclusions: All 12 of the 30 selected recipes (40%) demonstrated antihypertensive activity with the maximum decrease of MABP at 27.17±3.17% that was 2.41-fold of prazosin hydrochloride. Most recipes exhibiting antihypertensive activity contained plants in the families of Zingiberaceae and Piperaceae. The top five antihypertensive recipes showed the presence of glycosides, xanthones and alkaloids. Ten single plants from these recipes were extracted and evaluated for antihypertensive activity. The cassumunar ginger extract exhibited the maximum decrease of MABP at 39.83±3.92%, which was 3.54-times that of prazosin hydrochloride. This study demonstrated the potent antihypertensive activity of Thai medicinal plants and recipes that can be further developed as antihypertensive agents. © 2013 Informa Healthcare USA, Inc.